PROFIL KEMAMPUAN BERPIKIR KRITIS MAHASISWA PENDIDIKAN KIMIA DALAM MENYELSAIKAN PERMASALAHAN KONTEKSTUAL PADA MATERI TERMOKIMIA - Lusi, Yohana; Sahputra, Rachmat; Rasmawan, Rahmat (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2023)
This study aims to find out the critical thinking skills of chemistry education students in completing questions in the form of contextual problems. The research form used is descriptive qualitative research using a contextual problem test in the form of 4 essay questions. It is categorized as qualitative descriptive research since this research focuses only to know the level of students' critical thinking skills in solving contextual problems. The research participants are second-year university students. The results of this study indicate that the critical thinking skills of chemistry education students in solving thermochemical questions in the form of contextual problems with indicators of interpreting information, making generalizations, creating assumptions, and thinking inductively are respectively 48.33%, 40.00%, 20.00 %, and 43.33%. From the results of the study, it can be concluded that the critical thinking skills of chemistry education students in solving contextual problems are categorized as low instead.